Penerapan Scaffolding dalam Pembelajaran untuk Meningkatkan Kreativitas Peserta Didik dalam Eksplorasi Pewarnaan Batik Teknik Colet - Suryani, Leny; Al Hazmi, Fariz; Hafiizh Ash Shiddiqi (IAI Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the application of scaffolding in batik coloring techniques using the colet method to enhance students' creativity in exploring batik colors. A qualitative approach was employed, utilizing saturated sampling techniques with grade 6 students of SDN Bantarwaru II as the sample. Data were collected through observation and analyzed using Miles and Huberman's data analysis model. The results show that the implementation of scaffolding significantly positively influenced students' creativity, as reflected in the aspects of fluency, flexibility, originality, and elaboration. Scaffolding enabled students to develop technical skills, think more creatively, and apply colors and batik motifs more freely and originally. Although the aspect of originality still presents challenges, overall, students' creativity reached an average score of 84.8%. In conclusion, scaffolding is effective in supporting batik learning and enhancing students' creativity. It can be further implemented with the development of learning media that supports deeper cultural exploration.